2013
DOI: 10.1007/s00269-013-0585-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the solid acidity of heated and cation-exchanged montmorillonite using n-butylamine titration in non-aqueous system and diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy

Abstract: The effects of heating and cation exchange on the solid acidity of montmorillonite were investigated using n-butylamine titration in non-aqueous system and diffuse reflectance Fourier transform infrared spectroscopy. The number of total, Brønsted, and Lewis acid sites showed the same modulation tendency with increasing heating temperature, reaching a maximum at 120°C and subsequently decreasing until it reaches a minimum at 600°C. The Lewis acid sites result from unsaturated Al 3? cations, and their number inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…[ 16 ] Therefore, natural MMT usually shows Brønsted acidity rather than Lewis acidity. The pyridine infrared results of Reddy [ 16 ] and Liu [ 27 ] showed that only MMT treated with strong Lewis acid (NiCl 2 , ZnCl 2 , FeCl 3 , AlCl 3 ) showed strong PyL and PyH + vibration peaks. However, PyL peak was much weaker and even negligible compared with PyH + pak in the native MMTs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 16 ] Therefore, natural MMT usually shows Brønsted acidity rather than Lewis acidity. The pyridine infrared results of Reddy [ 16 ] and Liu [ 27 ] showed that only MMT treated with strong Lewis acid (NiCl 2 , ZnCl 2 , FeCl 3 , AlCl 3 ) showed strong PyL and PyH + vibration peaks. However, PyL peak was much weaker and even negligible compared with PyH + pak in the native MMTs.…”
Section: Resultsmentioning
confidence: 99%
“…The water content was determined by measuring the mass loss of samples dried at 120°C for 24 h, which was mainly attributed to surface‐adsorbed water. [ 27 ] The sufficient surface‐adsorbed water indicated that all of the interlayer cations were coordinated by interlayer water. Since Brønsted acidity mainly depended on the hydration ability of interlayer cations, the sufficient surface‐adsorbed water in the MMTs caused negligible effect of water content on the Brønsted acidity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of some binders is debatable because of the complex process involving a combination of porosity characteristics, surface acidity, temperature, pH and distribution of exchangeable cations . For instance, Johnston et al conducted a study that investigated glucomannon (MTB‐100) as a possible agent for sequestering aflatoxin in contaminated dried distillers grains (DDGs), resulting in an 80% reduction in total aflatoxin levels.…”
Section: Binding Agents For the Reduction Of Aflatoxinsmentioning
confidence: 99%